2012
DOI: 10.4149/bll_2012_034
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of ketamine and propofol in obstructive jaundice: an experimental study

Abstract: Abstract:Objective: In this study, we investigated the protective effects of frequently used intravenous anesthetics (ketamine, propofol, thiopental, and fentanyl) in oxidative stress in a rat liver model of obstructive jaundice. Materials and methods: Thirty-two Wistar albino rats were divided into four groups in a randomized fashion. All rats were subjected to laparotomy, common bile duct ligation and severance on day 0. Following 7 days, laparotomy was again performed using ketamine, propofol, pentobarbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Neutrophil migration and toxic biliary products start the generation of oxygen free radicals, thus unbalancing the antioxidant status in the liver. Antioxidant defenses, as demonstrated by GSH, catalase and SOD, are found to be decreased while lipid peroxidation, as demonstrated by MDA levels, is found to be increased in rat models with OJ (7,18,19). There have been studies suggesting that LA reduced MDA levels and increased antioxidant levels such as GSH and SOD in hepatic pathologies (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 96%
“…Neutrophil migration and toxic biliary products start the generation of oxygen free radicals, thus unbalancing the antioxidant status in the liver. Antioxidant defenses, as demonstrated by GSH, catalase and SOD, are found to be decreased while lipid peroxidation, as demonstrated by MDA levels, is found to be increased in rat models with OJ (7,18,19). There have been studies suggesting that LA reduced MDA levels and increased antioxidant levels such as GSH and SOD in hepatic pathologies (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 96%
“…Antioxidant defence (as demonstrated by CAT and SOD activities) is diminished and lipid peroxidation (as demonstrated by MDA levels) is increased during extrahepatic OJ in rat models. 17 , 18 Tissue damage associated with OJ may be caused by accelerated generation of hydroxyl radicals. Many clinical observations and experimental studies point to the frequent occurrence of different organ complications in patients with OJ.…”
Section: Discussionmentioning
confidence: 99%
“…However, excess accumulation of ROS induces a chain of reactions in cardiovascular pathological processes such as hypertension, ischemia/reperfusion injury (20). It has been reported that markers of oxidative stress (such as malondialdehyde, superoxide dismutase and catalase) are affected by ketamine and thiopental to different degrees (21).…”
Section: Discussionmentioning
confidence: 99%